Iowa Birdline update, August 7, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for August 7, 1989. Highlights include shorebird migration and a Peregrine Falcon release. Epson - sheet feed/flatbed